Hubungan Kepuasan dan Kepercayaan terhadap Loyalitas Konsumen Kopi Bubuk Cap Mutiara Pendekatan Structural Equation Modeling - I PUTU BAYU SUKMA ARI YOGA; GUSTI AYU OKA SURYAWARDANI; I GUSTI AYU AGUNG LIES ANGRENI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2016)
Abstract Relationship of Satisfaction and Truston Customer Loyalty of Mutiara Coffee. Structural Equation Modeling Approach Mutiara coffee is one of the original Pupuan coffee products which has been produced since 1976. Understanding the relationship between satisfaction and trust on the customer loyalty is essential to assess repeat buying of customer on products or service.This research was designed to determine factors that influence of satisfaction, trust, and loyalty on customer of Mutiara coffee and the relationship of satisfaction and trust on customer loyalty of Mutiara coffee. Structural Equation Modeling (SEM) was designed to understand, with AMOS 22 and SPSS 22 was used to analysis the relations between satisfaction, trust, and loyalty.The results showfactors influences of customer satisfaction are taste, ready to be served, packaging, distribution, price, and promotion of Mutiara coffee. Factors that influence of customer trust are the image, costumer benefits, and honesty of Mutiara coffee. Factors that influence of customer loyalty are rebuy, word of mouth communication, and no brand switching. Customer satisfaction has asignificant relationship on customer loyaltyof Mutiara coffee (p = 0,000) with the estimated value = 0,664 (? 0,5). Customer trusthas asignificant relationship on customer loyalty of Mutiara coffee (p = 0.006) with the estimated value = 0,512 (? 0,5). Customer satisfaction has a significant correlation with costumer trust (p = 0,000) with the estimated value = 0,674 (? 0,5).